Immediate release drug delivery systems: a current update - Saha, Suman (Creative Pharma Assent, 2018)
Instead of tremendous advancements in drug delivery, the oral route remains the most preferred route for the administration of therapeutic agents because of the low cost of therapy and ease of administration that leads to high levels of patient concordance. Incorporating an existing medicine into Newer Drug Delivery System (NDDS) are gaining popularities. One such approach is to formulate Immediate Release Tablet, which dissolve or disintegrate rapidly in saliva without the need of water within few seconds due to action of superdisintegrant in the formulation or other novel manufacturing technique. The demand for orally disintegrating tablets has enormously increased during the last decade over the other oral dosage forms (such as tablets, capsules, dry syrups, chewing gums, chewable tablets etc.) particularly for geriatrics and pediatrics, travelers, dysphasics, psychotics and non-cooperative patients. Considering the advantages of Immediate Release Tablet and its growing demand, an attempt has been made through this article to give an overview of preparation and new methodologies for the Immediate Release Tablet followed currently and in past including some patient information.